1296 E-waste recycling in canada – workers' exposure to metals and flame retardants. (24th April 2018) - Gravel, S; Bakhiyi, B; Bernstein, S; Diamond, ML; Jantunen, LM; Lavoie, J; Ngyuen, L; Roberge, B; Verner, M-A; Yang, C; Zayed, J; Labrèche, F
Abstract : Introduction: Electronic waste (E-waste) recycling is a booming industry. E-waste contains metals and flame retardants (FRs) that are released during dismantling processes, thus exposing workers. Several of these substances are associated with adverse health effects. The goal of this study is to assess occupational exposure to metals, brominated (BFR) and organophosphosphate ester (OPE) FRs in e-waste recycling facilities. Methods: Personal air sampling was performed over 8 hour work days with 10 workers in two companies. Analyses covered a dozen metals, BFRs and OPEs, including polybromodiphenyl ethers (PBDEs). Tasks and workstations were described through observation. Metals were analysed by inductively coupled plasma mass spectrometry, and flame retardants by gas chromatography and mass spectrometry. Concentrations below the limit of detection were imputed as LOD/√2. Results: The exposure levels for metals were below occupational exposure limits. Geometric means (GM) for air concentration were 918 ng/m 3 for copper [range: 487–2200], 346 ng/m 3 for lead [121–1000], 85 ng/m 3 for cadmium [60–240] and one positive sample for yttrium (970 ng/m 3 ). The highest PBDE concentration was for BDE-209 (GM=39 ng/m 3 [6–986]), and the highest OPE was tris (2-chloroethyl) phosphate (TCEP) (GM=156 ng/m 3 [80–478]). Lead concentrations were correlated with BDE-153, BDE-183, BDE-209 and tris(1, 3-dichloro-2-propyl) phosphate (TDCPP); Spearman's ρ of 0.70, 0.89, 0.80 and 0.71 (p<0.05), respectively. TDCPP levels were also correlated with BDE-183, copper and cadmium; Spearman's ρ of 0.77, 0.84 and 0.67 (p<0.05). Highest levels of BDE-153, BDE-209, TCEP, lead and yttrium were measured at the cathode ray tubes dismantling workstation. Conclusion: These results in E-waste recycling sites clearly show concomitant exposure to various metals and flame retardants, some of which predominate in certain workstations. Upcoming additional samples and their detailed task description will help identify activities and electronic items that may require more attention in e-waste management.